Citizen Participation of People with Disabilities and Intersectoral Public Policies Offered by the State in the Region of Magallanes, Chile - Solsona Cisternas, Diego; Flores Águila, Melissa (Revista del CLAD Reforma y Democracia, 2020)
The citizen participation of people with disabilities is part of a great challenge that is discursively positioned as a normative horizon in modern democratic societies: “inclusion”. Since 2006, the United Nations Convention on the Rights of Persons with Disabilities has established, among other priorities, that countries must ensure equal conditions for the participation of people with disabilities in political and public life. This paper analyzes the participation of people with disabilities in social and political life through the implementation of an intersectoral public policy offered by the State of Chile. The case of the Region of Magallanes, located in the extreme south of the country, is taken as reference. Through the action research methodology, the experiences of two programs offered by the State and executed by the University of Magallanes in 2016 and 2017, called “Inclusive Local Development Strategy” (EDLI in Spanish) and “Schools of Social and Territorial Management” (EGST in Spanish), are analyzed. Throughout the article, the territorial actors, strategies, characteristics of participation and their results in relation to the social inclusion of people with disabilities are identified. The document proposes elements to consider in the execution of actions that promote citizen participation of people with disabilities, emphasizing that their full inclusion in social life will never be a concession, but will depend on their participation, their capacity for self-organization, their strategies to make their demands visible, and on the articulation of territorial actors and organizations.
Keywords: Citizen Participation; Disabled Persons; Public Policy; Intersectoriality; Regions; Case Analysis; Chile